Continental-scale citizen science data reveal no changes in acoustic responses of a widespread tree frog to an urbanisation gradient. Issue 1 (4th February 2020) - Mitchell, Brittany A; Callaghan, Corey T; Rowley, Jodi J L
Abstract: One of the major drivers of global biodiversity declines is habitat loss and modification, often associated with anthropogenic environments. To mitigate biodiversity declines, a comprehensive understanding of how species respond to novel anthropogenic environments is required. Compared to natural habitats, human-modified environments often have increased noise and light pollution, potentially affecting acoustically communicating species, such as frogs. These areas may force animals to modulate or alter their calls to communicate with potential mates, as they compete with anthropogenic noise. Using large-scale citizen science data, coupled with remotely sensed data, we examined how the advertisement calls of the Australian red tree frog ( Litoria rubella ) varied in response to a gradient consistent with anthropogenic disturbance. After measuring a suite of acoustic properties of L.rubella across its range, we discovered that their advertisement calls showed no response to a disturbance urbanisation gradient. The advertisement calls of the species were highly variable, both at continental and local scales. Our results indicate that acoustic communication in male L.rubella may not be impeded in human-modified habitats as (1) they are a loud species typically heard over background noise and multi-species choruses and (2) their calls are highly variable—potentially serving as a buffer to any acoustic disturbances. Overall, our results provide evidence that some frog species may be acoustically urban tolerant and provide a greater understanding of the responses frogs exhibit to human-mediated environmental change.